A risk scoring system for seafood supply chain breaches and examination of freshwater fish imported to Australia. (14th June 2021) - Williams, Michelle; Hernandez-Jover, Marta; Williams, Thomas; Shamsi, Shokoofeh
Abstract: Legislative changes have altered the way imported edible seafood is inspected in Australia. Greater onus of responsibility has been placed on exporting countries to provide documentary evidence of adherence to internally recognized food safety standards. According to global trade agreements, any additional safety tests applied to freshwater fish imported into Australia must be justified. Therefore, the aim of this study was to develop a risk scoring method to provide justification for identifying countries as 'Freshwater fish high risk' and to examine the seafood they export to Australia for seafood supply chain breaches. Scoring was conducted using six predictor variables, identified in the literature as important contributors to seafood supply chain breaches, to achieve the outcome variable, Country considered ' Freshwater fish high risk '. Sixty-seven fish fillets (9.55 kg) of the same species were examined from the third highest scoring country (Country 20) and 562 (5.6 kg) whole fish from the sixth highest scoring country (Country 22). Country 20 had supply chain breaches of 28 macroscopic yellow cysts in one fillet. Two hundred and thirteen parasites and other supply chain breaches were identified in fish from Country 22, including retained liver (91 per cent), visible mud (11 per cent), a variety of debris (16 per cent) and, depending on the commodity code, these fish were imported to Australia under full intestine (90 per cent), retained gills (89 per cent), and partial intestine (9 per cent). Three serious physical hazards were recovered from the edible portion of three 'consumer-ready' fish and snails of Genus Lymnaea and Indoplanorbis were recovered from gill mud also from 'consumer-ready' fish. The study showed variable results from the scoring system and vast differences in seafood supply chain breaches between the third and sixth highest scoring countries.